Current Progress and Future Directions for Theory and Research on Savoring - Bryant, Fred B. (Frontiers in Psychology, 2021)
As research on savoring has increased dramatically since publication of the book Savoring: A New Model of Positive Experience (Bryant & Veroff, 2007), savoring has gradually become a core concept in positive psychology. I begin by reviewing the evolution of this concept, the development of instruments for assessing savoring ability and savoring strategies, and the wide range of applications of savoring in the psychosocial and health sciences. I then consider important directions for future theory and research. To advance our understanding of how naturalistic savoring unfolds over time, future work should integrate the perceptual judgments involved in not only the later stages of noticing, attending to, and regulating positive experience (where past research has concentrated), but also the initial stages of searching for and detecting positive stimuli. Whereas most research has investigated reactive savoring, which occurs spontaneously in response to positive events or feelings, future work is also needed on proactive savoring, which begins with the deliberate act of seeking out or creating positive stimuli, rather than passively waiting until one happens to notice positive stimuli. To advance the measurement of savoring-related constructs, I recommend that future work move beyond retrospective self-report methods toward the assessment of savoring as it occurs in real-time. The development of new methods of measuring meta-awareness and the regulation of attentional focus are crucial to advancing our understanding of savoring processes. Research is also needed to learn more about what enhances savoring, and to disentangle how people regulate the intensity versus duration of positive emotions. I review recent psychophysiological research on the neurobiological correlates of savoring and suggest future directions in which to expand such work on the neurodynamics of savoring. Finally, I encourage future researchers to integrate the study of anticipation, savoring the moment, and reminiscence within individuals across time.